2022
DOI: 10.1108/tr-03-2022-0164
|View full text |Cite
|
Sign up to set email alerts
|

Adult children traveling with parents: exploring travel conflict and parents’ subjective well-being

Abstract: Purpose Drawing on solidarity-conflict model, expectancy disconfirmation theory and bottom-up spillover theory, this study aims to explore how intergenerational conflict is linked to parents’ subjective well-being through the serial mediating effects of family intimacy and travel satisfaction, self-efficacy and travel satisfaction. Design/methodology/approach Based on a survey of 411 senior parents who have family travel experience, a structural equation modeling was performed to test the hypotheses. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Moreover, measurement items were also significantly loaded to latent variable ( p < 0.001) (Table 1). The heterotrait–monotrait ratios were below 0.80 (Hu et al , 2022). The reliability of each construct ranged from 0.79 to 0.95, which demonstrated relatively high reliability compared to the suggested cut-off point of 0.70 (Nunnally and Bernstein, 1994).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, measurement items were also significantly loaded to latent variable ( p < 0.001) (Table 1). The heterotrait–monotrait ratios were below 0.80 (Hu et al , 2022). The reliability of each construct ranged from 0.79 to 0.95, which demonstrated relatively high reliability compared to the suggested cut-off point of 0.70 (Nunnally and Bernstein, 1994).…”
Section: Resultsmentioning
confidence: 96%
“…While prior studies have revealed that family tourists are likely to have emotional, experiential and high-quality tourism experiences (Backer and King, 2016; Chen et al , 2022; Hu et al , 2022), how family tourists’ emotional responses are formed at WHSs is not yet sufficiently understood (Chen et al , 2022). By investigating emotional responses with its antecedents and moderating relationships, the study contributes to literature by extending CAT into the context of family tourism at WHSs, which theoretically adds to the existing knowledge of family tourism, and practically provides managerial and marketing implications for WHSs tourism practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…For a considerable period, the discussion surrounding the connection between tourism and welfare has primarily focused on the micro-level analysis of whether tourists can derive happiness from their travel experiences. This includes the research on the disparities between various types of tourism activities in generating blissful tourism experiences [10][11][12], the pathways to enhancing blissful tourism for tourism consumer groups with distinct characteristics [13][14][15], and the mechanism behind generating tourism happiness experiences [2,16,17]. Under the wave of the massification and popularization of tourism activities, the studies above have laid a solid foundation for the rational cognition of whether tourism possesses the attributes of a happiness industry.…”
Section: Introductionmentioning
confidence: 99%